SYNGAS PRODUCTION FROM CO2-REFORMING OF CH4 OVER SOL-GEL SYNTHESIZED Ni-Co/Al2O3-MgO-ZrO2 NANOCATALYST: EFFECT OF ZrO2 PRECURSOR ON CATALYST PROPERTIES AND PERFORMANCE - Seyed Mehdi Sajjadi; Mohammad Haghighi; Farhad Rahmani (Química Nova, 2015)
Ni-Co/Al2O3-MgO-ZrO2 nanocatalyst with utilization of two different zirconia precursors, namely, zirconyl nitrate hydrate (ZNH) and zirconyl nitrate solution (ZNS), was synthesized via the sol-gel method. The physiochemical properties of nanocatalysts were characterized by XRD, FESEM, EDX, BET and FTIR analyses and employed for syngas production from CO2-reforming of CH4. XRD patterns, exhibiting proper crystalline structure and homogeneous dispersion of active phase for the nanocatalyst ZNS precursor employed (NCAMZ-ZNS). FESEM and BET results of NCAMZ-ZNS presented more uniform morphology and smaller particle size and consequently higher surface areas. In addition, average particle size of NCAMZ-ZNS was 15.7 nm, which is close to the critical size for Ni-Co catalysts to avoid carbon formation. Moreover, FESEM analysis indicated both prepared samples were nanoscale. EDX analysis confirmed the existence of various elements used and also supported the statements made in the XRD and FESEM analyses regarding dispersion. Based on the excellent physiochemical properties, NCAMZ-ZNS exhibited the best reactant conversion across all of the evaluated temperatures, e.g. CH4 and CO2 conversions were 97.2 and 99% at 850 ºC, respectively. Furthermore, NCAMZ-ZNS demonstrated a stable yield with H2/CO close to unit value during the 1440 min stability test.